Biomechanical Evaluation With a Novel Cadaveric Model Using Supination and Pronation Testing of a Lisfranc Ligament Injury. Issue 1 (13th January 2020) - Wagner, Emilio; Wagner, Pablo; Baumfeld, Tiago; Prado, Marcelo Pires; Baumfeld, Daniel; Nery, Caio
Background: Lisfranc joint injuries can be due to direct or indirect trauma and while the precise mechanisms are unknown, twisting or axial force through the foot is a suspected contributor. Cadaveric models are a useful way to evaluate injury patterns and models of fixation, but a frequent limitation is the amount of joint displacement after injury. The purpose of this study was to test a cadaveric model that includes axial load, foot plantarflexion and pronation-supination motion, which could re-create bone diastasis similar to what is seen in subtle Lisfranc injuries. Our hypothesis was that applying pronation and supination motion to a cadaveric model would produce reliable and measurable bone displacements. Methods: Twenty-four fresh-frozen lower leg cadaveric specimens were used. The medial (C1) and intermediate (C2) cuneiforms and the first (M1) and second (M2) metatarsal bones were marked. A complete ligament injury was performed between C1-C2 and C1-M2 in 12 specimens (group 1), and between C1-C2, C1-M2, C1-M1, and C2-M2 in 12 matched specimens (group 2). Foot pronation and supination in addition to an axial load of 400 N was applied to the specimens. A 3D digitizer was used to measure bone distances. Results: After ligament injury, distances changed as follows: C1-C2 increased 3 mm (23%) with supination; C1-M2 increased 4 mm (21%) with pronation (no differences between groups). As expected, distances between C1-M1 and C2-M2 only changed in group 2, increasing 3 mm (14%) and 2 mm (16%), respectively (no differences between pronation and supination). M1-M2 and C2-M1 distances did not reach significant difference for any condition. Conclusions: Pronation or supination in addition to axial load produced measurable bone displacements in a cadaveric model of Lisfranc injury using sectioned ligaments. Distances M1-M2 and C2-M1 were not reliable to detect injury in this model. Clinical Relevance: This new cadaveric Lisfranc model included foot pronation-supination in addition to axial load delivering measurable bone diastasis. It was a reliable Lisfranc cadaveric model that could be used to test different Lisfranc reconstructions.